LCA of fishing vessels exporting fish from the Arctic. - Oveisi, Shima; Moeinaddini, Mazaher; Natcher, David (Science of The Total Environment, 2025)
The commercial fishing industry, particularly in remote regions like the Canadian Arctic, has seen increasing pressure due to the growing demand for seafood and concomitant declines in other global fishing stocks. Fishing vessels, which are critical in transporting fish from these regions to international markets, have significant environmental impacts that contribute to global warming. This study evaluates the environmental impacts of Canadian Arctic fishing vessels through Life Cycle Assessment, focusing on diesel fuel consumption, packaging materials, and operational factors such as water and electricity use. The results indicate that diesel fuel use accounts for 89.2 % of the total global warming potential (6.26 kg CO₂ eq per kg of fish), making it the dominant contributor to emissions. Additionally, diesel combustion contributes significantly to fossil resource depletion (1.09 kg oil eq) and terrestrial acidification (0.14 kg SO₂ eq). Packaging materials, particularly polyethylene and waste paperboard, contribute to marine ecotoxicity (0.0031 kg 1,4-DCB) and resource depletion, while water consumption influences freshwater eutrophication (0.00019 kg P eq). Despite their smaller contribution compared to fuel use, these inputs still play a notable role in the environmental footprint of fishing vessel operations. The sensitivity analysis revealed that a 10 % reduction in diesel consumption could decrease fossil resource scarcity by 8.4 %, marine ecotoxicity by 8.08 %, and global warming potential by 0.51 %, highlighting the potential for targeted efficiency improvements. These findings underscore the need for sustainable strategies, including fuel efficiency improvements, alternative energy sources, and optimized packaging waste management, to mitigate the environmental footprint of Arctic fishing operations.